Media Lagu dalam Pembelajaran IPS untuk Meningkatkan Motivasi Belajar Siswa Kelas V SDN Kertajaya IV/210 Surabaya - Nuriyah Khoirun Nisa', Rose Aninda; Mariati, Pance; Akhwani, Akhwani; Djazilan, Syukron (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
Learning media is often used in the implementation of effective learning so that students can be more involved in the classroom. However, many teachers continue to use traditional teaching methods, causing students to be less engaged in learning. Teachers can use song media as one of the learning media. The purpose of this study was to (1) analyze the research planning stages of using song media in social studies learning in class V SDN Kertajaya IV/210 Surabaya. (2) Describe the results of the use of music media in social studies learning on the learning motivation of fifth grade students at SDN Kertajaya IV/210 Surabaya. This study used qualitative research methods. The subjects of this study were 20 fifth grade students. This study uses primary data sources. Data collection techniques include observation, interviews, tests, questionnaires, and documentation. Test the validity of the data using technical triangulation. Data reduction, data presentation, and drawing conclusions are the data analysis techniques used. The results of the study revealed that social studies learning with the media of European arrival historical songs included three stages, namely planning, implementation, and evaluation. Learning planning consists of 2 stages: observation and study of literature. The stages of learning implementation are divided into three parts, namely preparatory activities, core activities, and closing activities. Learning is carried out at the assessment stage by examining achievements and deficiencies that occur during the learning process. The use of music media in social studies learning shows that the learning process runs smoothly and has the potential to increase student learning motivation.